Multipl Reentry Gunshot Wounds at Abdomen by a Single Shot Case Report - Uysal, Cafer; Boran, Tansev; Dokgöz, Halis; Uzun, Mustafa; Koç, Sermet (The Bulletin of Legal Medicine, 2001)
In this report a woman, who had been infured by a gunshot from her head and abdomen and died in a few hours in hospital is presented. In autopsy, none of the six gunshot wounds at abdomen is in relation with the abdominal cavity. Altough the gunshot wounds at abdomen are not on the same line, each of the wounds is related with the other. In order to show that all of the six gunshot wounds at the abdomen, was caused by only one shot, suitable position was given to the body regarding the abdominal fat layer, because the woman is very fat. Information taken from the detectives and the number of the entry wounds on two other persons who had died in the same event showed that the gunshot wounds at the abdomen had been caused by only one shot. This report is presented to discuss the mechanism of multipl reentry wounds and principles of approachment to this kind of cases. Key words: Gunshot wounds, reentry gunshot wounds.